Menggagas Pembatasan Pembentukan Dan Materi Muatan Perppu: Studi Perbandingan Pengaturan Dan Penggunaan Perppu Di Negara-Negara Presidensial - Arsil, Fitra (UI Scholars Hub, 2018)
Government regulation in lieu of law or ‘Perppu’arrangement in Indonesia is more limited than other types of emergency regulations issued by the president in various countries. Such arrangement apprently is not sufficient to be considered as limiting the issuance of the emergency regulations. Some presidential state countries have made changes to provide sufficient restrictions to presidential legislative power. The limitation is not only in terms of its formation procedures but also on the material which can be regulated by the Perppu. Therefore, lessons from other jurisdictionsindeed inspires Indonesia to limit the pasage of Perppu